Numerical research on flow field structure and droplets distribution of kerosene-fueled rotating detonation ramjet engine - Yushan, Zheng; Yu, Liu; Chao, Wang; Yitian, Wang (Aerospace science and technology, 2024)
•A self-sustaining periodic propagation detonation wave is obtained in the two-phase rotating detonation ramjet flow field and flow field distributions are described in detailed.•A triangular distribution of "rich oil and poor oxygen band" is found in the flow field and the formation mechanism is revealed. It is show that inconsistency in the recovery speed of air and fuel filling in rotating detonation ramjet is considered as the main reason, which is caused by the high-pressure environment after the detonation wave.•Difference of detonation flow field is analyzed under different orifice spacing. Obvious strip structures are seen when increasing the orifice spacing and n-type deflagration distributions are seen on the contact surface. Discontinuity of detonation wave is also seen, accompanied by strip-shaped deflagration behind the wave.•A detailed description of the distribution of kerosene droplets is provided and several groups are divided based on their characteristics. Obvious separation and aggregation phenomena of droplets are discovered and the formation mechanism is also described in detail. In order to reveal the multiphase flow field structure and fuel droplets distribution under rotating detonation ramjet engine fueled by liquid kerosene, non-premixed simulations coupled with an Euler-Lagrangian approach is adopted. Supersonic air is used as oxidizer and the total pressure and total temperature at the entrance of isolation are set as 1.2 MPa and 1100 K, respectively, with a Mach number of 1.9. It is shown that a single-wave is formed and typical rotating detonation wave structures are established under two different orifice spacing conditions, namely 2 mm and 6mm. A "rich oil and poor oxygen band" is formed and attributed to the inconsistent supply of fuel and air after the passage of the detonation wave. When the orifices spacing is increased from 2 mm to 6 mm, both obvious strips after the detonation wave and “n-type” deflagration structures near the contact surface are observed. Besides, the detonation wave front becomes discontinuous, as well as from the deflagration heat release distribution. Despite of the effect of the circumferential propagation of detonation wave, kerosene droplets still propagate mainly along the downstream direction. However, Kerosene droplets distribution shows obvious difference along the detonation wave propagation direction.